SISTEM INFORMASI PENGENDALIAN ASSET KENDARAAN DI PERUSAHAAN TRANSPORTASI - Donny Sanjaya; Hafizh Abdurachman; Austin Arif Wicaksono; Fajar Masya (LPPM Universitas Abdurrab, 2021)
The process of controlling assets in a company is often constrained because of the lack of tools and systems. To facilitate the control of assets owned by the company in reducing the budget, a web-based application was made with the name